How to promote the development of nurses’ moral competence according to patient representatives: a European qualitative study - Galazzi, Alessandro; Stolt, Minna; Papastavrou, Evridiki; Stefanopoulos, Nikos; Dimitriadou, Maria; Wiisak, Johanna; Keogh, Brian; Chiappinotto, Stefania; McCabe, Catherine; Suhonen, Riitta; Gastmans; Chris; et al. (John Wiley & Sons, 2026)
Aim:
To explore (a) how nurses can be supported in developing their moral competence and (b) which tools should be used, according to the perspective of patient representatives.
Background:
Nurses must provide morally competent care. Examining how moral competence can be developed requires a comprehensive approach that includes patients and their representatives to complement the perspective of professionals (e.g., educators).
Methods:
A descriptive qualitative multinational study in 2023 as part of the Promoting a Morally Competent Nurse (PROMOCON) project. A purposive sample of 35 patient representatives as members or chairs of patient organisations representing different diseases or health issues in Belgium, Cyprus, Finland, Greece, Ireland and Italy. Data were collected through focus group interviews and analysed using a thematic and content analysis approach. The checklist of the Consolidated Criteria for Reporting Qualitative Research was followed.
Results:
The development of nurses’ moral competence can be supported at three different levels, namely (1) at the societal level: “Recognition of the nursing profession”; (2) at the organisational level: “Building organisations based on ethically sound premises”; and (3) at the level of individual relationships: “Working on oneself to achieve moral competence in relation to oneself and others”. To support the development of morally competent nurses, various educational measures, infrastructures and social tools were recommended.
Conclusion:
In this area, a systematic approach is required that includes multicomponent strategies and is complemented by practical tools.